Characterization of Entire Sequences via Double Orlicz Space - N. Subramanian; R. Nallaswamy; N. Saivaraju (International Journal of Mathematics and Mathematical Sciences)
Let Γ denote the space of all entire sequences and ∧ the space of all analytic sequences. This paper is a study of the characterization and general properties of entire sequences via double Orlicz space of ΓM2 of Γ2 establishing some inclusion relations.